2010
DOI: 10.1002/mus.21891
|View full text |Cite
|
Sign up to set email alerts
|

Continuous endurance‐type exercise training does not modulate satellite cell content in obese type 2 diabetes patients

Abstract: Endurance-type exercise training represents a cornerstone in type 2 diabetes treatment. However, the effects of prolonged continuous, endurance-type exercise on muscle fiber characteristics remain equivocal. Fifteen obese male type 2 diabetes patients (61 6 6 years) participated in a 6-month continuous, endurance-type exercise program. Muscle biopsies were collected before, and after 2 and 6 months of intervention. Muscle fiber type-specific composition, size, and satellite cell (SC) and myonuclear content wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 54 publications
(125 reference statements)
4
35
1
1
Order By: Relevance
“…Given the induction of muscle hypertrophy using the training protocols with high‐intensity bouts of exercise, it is plausible that high‐intensity type activity for prolonged periods of time may induce hypertrophy and hence SC activity. In addition, each study reporting on the expansion of the SC pool following endurance type training in humans reported no change in fiber type distribution (2022). This further highlights the fact that the expansion of the SC pool associated with training likely resulted from muscle hypertrophy and was not due to a fiber‐type transition induced by training.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Given the induction of muscle hypertrophy using the training protocols with high‐intensity bouts of exercise, it is plausible that high‐intensity type activity for prolonged periods of time may induce hypertrophy and hence SC activity. In addition, each study reporting on the expansion of the SC pool following endurance type training in humans reported no change in fiber type distribution (2022). This further highlights the fact that the expansion of the SC pool associated with training likely resulted from muscle hypertrophy and was not due to a fiber‐type transition induced by training.…”
Section: Discussionmentioning
confidence: 85%
“…Both studies reporting an increase in SC content following training had training protocols consistent with interval‐type training in which subjects completed 4 min of low‐intensity cycling followed by 1 min of high‐intensity cycling for a total of 40–45 min 3–4 d/wk for 14 wk (20, 21). The study that reported no change in SC content had a more modest endurance training protocol, in which subjects completed 40 min of low‐intensity exercise 3 d/wk for 6 mo (22). Given the induction of muscle hypertrophy using the training protocols with high‐intensity bouts of exercise, it is plausible that high‐intensity type activity for prolonged periods of time may induce hypertrophy and hence SC activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Other studies showed no difference with resistance training in older women 11 or continuous endurance-type exercise in obese patients with type 2 diabetes. 12 Many athletic trainers and others advocate the use of branched-chain amino acid (BCAA) supplementation during exercise training. BCAA supplementation decreases muscle damage associated with resistance training.…”
Section: Introductionmentioning
confidence: 99%
“…After a 14-wk training period, the numbers of NCAM-positive satellite cells increased in both upper and lower limb muscles, whereas the numbers of myonuclei were unchanged 102) . Recently, Snijders et al reported that a 6-month endurance-type exercise did not alter the number of satellite cells in muscles of type 2 diabetes patients 103) . Although further studies are needed, endurance exercise appears to stimulate, to some extent, the proliferation of satellite cells in healthy subjects.…”
Section: Effect Of Resistance Training On Satellite Cell Numbermentioning
confidence: 98%